Enhancing shared and surrogate decision making for people living with dementia: A systematic review of the effectiveness of interventions. (28th November 2020) - Geddis‐Regan, Andrew; Errington, Linda; Abley, Clare; Wassall, Rebecca; Exley, Catherine; Thomson, Richard
Abstract: Background: Dementia can have a profound impact on decision making. People living with dementia (PLwD) often need to make decisions about health care, and, as dementia progresses, decisions may need to be made on their behalf. Specific interventions may support this process. Review Question: What interventions are effective in improving shared decision making or surrogate decision making on the health care of PLwD? Methods: A narrative systematic review of existing literature was conducted. Seven databases, grey literature and key journals were searched. After exclusion by title, abstracts then full texts were reviewed collaboratively to manage any disagreements. Results: Eight studies met the inclusion criteria. Two articles, including one RCT, evaluated decision aids regarding the use of enteral feeding in advanced dementia. Six further articles, including five RCTs, were found which evaluated the effectiveness of interventions supporting patients or carers with advance care planning. Conclusion: Decision‐making interventions typically consist of multiple components which aim to establish preferences for future health care. Advance care planning interventions supported aspects of the decision‐making processes but their impact on decision quality was rarely evaluated. Interventions did not increase the concordance of decisions with a person's values. The decision‐specific interventions are unlikely to produce benefit in other decision contexts. Patient Involvement: Two caregivers, a public stakeholder group and a carer group were consulted in the design of the wider study to which this review relates. Six PLwD refined the research questions addressed in this paper.